Modern Debugging: The Art of Finding a Needle in a Haystack. - SPINELLIS, DIOMIDIS (Communications of the ACM, 2018)
The article presents several tools to be used in the process of debugging software. It mentions searching for previous reports of problems and the solutions offered, the testing of software components during the coding process, and the creation of practices that facilitate debugging.